Verhochdeutschung von Toponymen der Deutschschweiz seit dem 19. Jahrhundert - Thöny, Luzius; Schneider, Thomas Franz (Linguistik Online, 2023)
The diglossia in German-speaking Switzerland affects many aspects of language use of the speakers of this area, among them the question of how to render toponyms in writing. In the 19th century, toponyms were generally transposed from spoken Swiss German to Standard German. In this article, we discuss the main strategies of this transposition in the two main sources of toponomastic data for the canton of Bern in the 19th century, i. e. the gazetteer by Durheim and the so-called Siegfriedkarte (the predecessor of the modern official map, the Landeskarte). We also discuss some errors made by their authors when transposing the names, e. g. by mistakenly reverting certain dialectal changes (hypercorrection) or by semantic reanalysis. In the middle of the 20th century, a new regulation issued by the Swiss authorities mandated that toponyms should generally be spelled in accordance to how they are spoken by the local population. This new regulation was implemented for local names, i. e. names of fields, forests, rivers, small settlements etc., but not for names of larger settlements, well-known mountains, rivers or regions, resulting in some inconsistencies which persist on the official maps until today. An initiative implemented by some cantons in the early 21st century to render spoken dialect features more accurately in the spelling of toponyms had to be abandoned because of the resistance of the local population. Until today, and likely also in the future, the spellings of toponyms of German-speaking Switzerland vacillate between adherence to the orthography and sound patterns of (Swiss) Standard German, on the one hand side, and an accurate representation of spoken Swiss German dialect forms, on the other.